ASEAN in the World’s 100 Top-Ranked Pension Funds: Lessons for Indonesia - Asshagab, Sri Milawati; Hasanah, Asia Miscolayati (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2024)
The research explored the pension funds of Singapore, Malaysia, and Vietnam, which had managed to exceed Indonesia’s total pension fund assets under management despite having smaller populations and workforces. With Indonesia aiming to increase its pension funds to 60% of its GDP by 2045, the research aimed to extract lessons from the investment strategies, governance structures, and other key indicators of the pension funds in these three ASEAN countries to aid in achieving Indonesia’s target. This research utilized a document analysis method to gather data on top-ranking pension funds in ASEAN countries, including the Central Provident Fund (Singapore), Employees Provident Fund (Malaysia), Social Insurance Funds (Vietnam), and BPJS Ketenagakerjaan (Indonesia), with qualitative and descriptive statistics methods employed for data analysis. This research has found that Singapore and Malaysia excel in managing their pension fund accounts by offering innovative services tailored to meet the needs of their citizens. Singapore has special home ownership and asset management accounts with a strong social media presence. Malaysia offers both conventional and Sharia-based services, including services for the hajj, which cater to the religious needs of its Muslim population. Meanwhile, Vietnam has a more inclusive system that covers foreign workers, similar to Indonesia’s, but demands that foreign workers join the program should align with available program information in English.